2019
DOI: 10.1093/eurheartj/ehz185
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of ticagrelor vs. aspirin in patients after coronary artery bypass grafting: the TiCAB trial

Abstract: Aims The antiplatelet treatment strategy providing optimal balance between thrombotic and bleeding risks in patients undergoing coronary artery bypass grafting (CABG) is unclear. We prospectively compared the efficacy of ticagrelor and aspirin after CABG. Methods and results We randomly assigned in double-blind fashion patients scheduled for CABG to either ticagrelor 90 mg twice daily or 100 mg aspirin (1:1) once daily. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 42 publications
0
42
0
3
Order By: Relevance
“…For clinical (secondary) outcomes, the results of our network meta-analysis show no differences in effect estimates among multiple treatment comparisons; nonetheless, these were not our prespecified primary outcomes. Interestingly, the recently published and prematurely terminated trial that compared ticagrelor with aspirin after coronary artery bypass graft surgery showed no important differences in major adverse cardiovascular events or bleeding between the monotherapies 50. These findings support the need for studies that evaluate dual antiplatelet therapy after coronary artery bypass graft surgery.…”
Section: Discussionmentioning
confidence: 80%
“…For clinical (secondary) outcomes, the results of our network meta-analysis show no differences in effect estimates among multiple treatment comparisons; nonetheless, these were not our prespecified primary outcomes. Interestingly, the recently published and prematurely terminated trial that compared ticagrelor with aspirin after coronary artery bypass graft surgery showed no important differences in major adverse cardiovascular events or bleeding between the monotherapies 50. These findings support the need for studies that evaluate dual antiplatelet therapy after coronary artery bypass graft surgery.…”
Section: Discussionmentioning
confidence: 80%
“…Ticagrelor, a “next generation” P2Y12 receptor inhibitor is an alternative antiplatelet therapy commonly prescribed to patients with CAD. It has demonstrated its efficacy as an antiplatelet medication when compared with ASA and clopidogrel [ 20 , 43 ]. The THEMIS trial conducted by Steg et al in 2019 demonstrated that patients with stable CAD and diabetes benefited from taking ticagrelor in combination with ASA, compared to ASA and a placebo [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…trial did not demonstrate an advantage of adding ticagrelor to aspirin in patients fresh after coronary bypass surgery. 33 One of the most interesting observations, this year, came from the Swedeheart registry, where the investigators demonstrated a 40% risk reduction in mortality by using statins (and also using renin-angiotensin-aldosterone system inhibitors) postoperatively (►Fig. 2D).…”
Section: The Role Of Medical Therapy In Cabg Patientsmentioning
confidence: 99%